Study guides

Q: 1 half equals14 divided by 6x minus 2 minus 6 divided by 3x minus 1?

Write your answer...

Submit

Related questions

x^2 + 3x + 2/(-3x) - x^2 - 2=3x-2+2/(-3x)=3x-2-2/(3x)

(3x2 - 6x)/3x = 3x(x-2)/3x = x-2, for x<>0

6x-3x =6 3x=6 so 6 divided by 3 = 2

(x - 3x - 6) / 6 = (3x + 2) / 2 ∴2(3x + 2) = 6(3x + 2) ∴6x + 4 = 18x = 12 ∴12x = -8 ∴x = -2/3

If: 5/3x - 4/3x - 1 = 8 Then: x = 1/27

24

3x

Factorise it: (x + 5)(3x - 8)

-(3x-4) = -3x + 4

3x squared minus 25x minus 28

(x - 4)(3x + 5)

(x-3)(3x+1)

3x - 12 = 10x - 15 - 6x -10 3x - 12 = 4x -25 3x + 13 = 4x 13 = 4x - 3x 13 = x None?

That factors to 3x(3x - 1)

Locate the turning point(s) for the following functions. (a) y=x3-x2 -3x + 5 3

(3x + 1)(x - 5)

2x - 3x = -x

(x + 3)(3x - 2)

4/x - 1 + 6/3x +1 = 15/3x + 1 4/x - 1 + 2/x +1 = 5/x + 1 4/x + 2/x - 5/x = 1 + 1 -1 1/x = 1 x = 1

The question contains an expression but not an equation or inequality. There is, therefore, nothing to solve!

(3x + 1) = -3 (x + 2x -1) (3x + 1) = -3 (3x - 1) 3x + 1 = -9x + 3 12x = 2 6x = 1 x = 0.16666666666666666666666666666666666666666666666666666666666666666666

(3x4 + 2x3 - x2 - x - 6)/(x2 + 1)= 3x2 + 2x - 4 + (-3x - 2)/(x2 + 1)= 3x2 + 2x - 4 - (3x + 2)/(x2 + 1)where the quotient is 3x2 + 2x - 4 and the remainder is -(3x + 2).

2x^3 - 3x^2 + 4x - 3

9x2-9x-10 = (3x+2)(3x-5) when factored

x2-3x-10 = (x+2)(x-5) when factored